Haemoglobin Phenotypes In Balami And Uda Sheep Of Nigeria (2010)
Haemoglobin polymorphism was studied in Nigerian indigenous sheep. Blood samples were collected from 30 Balami and 30 Uda sheep randomly selected using jugular vein puncture and were analysed by the method o f cellulose acetate electrophoresis to reveal the Haemoglobin (HB) genetic types. Two co-dominant alleles (A and B) controlling three phenotypes (AA. AB and BB) were revealed by the cellulose strip in the sheep population. The frequencies o f allele A and B for Uda sheep were 0.10 and 0.90 while that for the Balami was 0.25 and 0.75 respectively